Estimación de la tasa de favoritismo en la elección presidencial mediante el uso del estimador de Regresión Local Polinomial (2009)
Several sampling strategies for estimating the popularity rating of a presidential candidate in the colombian elections of 2006, using Local Polynomial Regression Estimators in the ﬁrst stage of sampling, are proposed and evaluated. The oﬃcial data records of the 2002 colombian elections are used as the auxiliary information. The performance of these sampling strategies is evaluated by calculating the expectation and the variance of each estimator by non-analytical methods.